Absence of Replication of Porcine Endogenous Retrovirus and Porcine Lymphotropic Herpesvirus Type 1 with Prolonged Pig Cell Microchimerism after Pig-to-Baboon Xenotransplantation - Issa, Nicolas C. (American Society for Microbiology (ASM), 2008)
Porcine endogenous retrovirus (PERV), porcine cytomegalovirus (PCMV), and porcine lymphotropic herpesvirus (PLHV) are common porcine viruses that may be activated with immunosuppression for xenotransplantation. Studies of viral replication or transmission are possible due to prolonged survival of xenografts in baboon recipients from human decay-accelerating factor transgenic or α-1,3-galactosyltransferase gene knockout miniature swine. Ten baboons underwent xenotransplantation with transgenic pig organs. Graft survival was 32 to 179 days. Recipient serial samples of peripheral blood mononuclear cells (PBMC) and plasma were analyzed for PCMV, PERV, and PLHV-1 nucleic acids and viral replication using quantitative PCR assays. The PBMC contained PERV proviral DNA in 10 animals, PLHV-1 DNA in 6, and PCMV in 2. PERV RNA was not detected in any PBMC or serum samples. Plasma PLHV-1 DNA was detected in one animal. Pig cell microchimerism (pig major histocompatibility complex class I and pig mitochondrial cytochrome c oxidase subunit II sequences) was present in all recipients with detectable PERV or PLHV-1 (85.5%). Productive infection of PERV or PLHV-1 could not be demonstrated. The PLHV-1 viral load did not increase in serum over time, despite prolonged graft survival and pig cell microchimerism. There was no association of viral loads with the nature of exogenous immune suppression. In conclusion, PERV provirus and PLHV-1 DNA were detected in baboons following porcine xenotransplantation. Viral detection appeared to be due to persistent pig cell microchimerism. There was no evidence of productive infection in recipient baboons for up to 6 months of xenograft function.